2020
DOI: 10.3389/fncel.2020.592213
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Number of Required Inputs for Temporally Precise Action Potential Generation in Auditory Brainstem Nuclei

Abstract: The auditory system relies on temporal precise information transfer, requiring an interplay of synchronously activated inputs and rapid postsynaptic integration. During late postnatal development synaptic, biophysical, and morphological features change to enable mature auditory neurons to perform their appropriate function. How the number of minimal required input fibers and the relevant EPSC time course integrated for action potential generation changes during late postnatal development is unclear. To answer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 81 publications
(134 reference statements)
3
10
0
Order By: Relevance
“…1B, inset). Non-NMDAR-mediated currents reversed at 0 mV and showed strong inward rectification, in agreement with earlier results (Kladisios et al, 2020). This suggests that mainly GluR2 lacking AMPARs known from other auditory brainstem nuclei (Geiger et al, 1995;Lujan et al, 2019;Franzen et al, 2020) are underlying the adaptation of rapid synaptic transmission.…”
Section: Pharmacological Composition Of Glutamatergic Endbulb Currentssupporting
confidence: 91%
See 2 more Smart Citations
“…1B, inset). Non-NMDAR-mediated currents reversed at 0 mV and showed strong inward rectification, in agreement with earlier results (Kladisios et al, 2020). This suggests that mainly GluR2 lacking AMPARs known from other auditory brainstem nuclei (Geiger et al, 1995;Lujan et al, 2019;Franzen et al, 2020) are underlying the adaptation of rapid synaptic transmission.…”
Section: Pharmacological Composition Of Glutamatergic Endbulb Currentssupporting
confidence: 91%
“…Previous studies in auditory brainstem neurons have shown that a stimulus waveform influences action potential current thresholds (Cathala et al, 2003;Couchman et al, 2010;Ammer et al, 2012;Lehnert et al, 2014;Franzen et al, 2015;Cao and Oertel, 2017;Kladisios et al, 2020;Bondy et al, 2021). Since VNLL EPSCs exhibited biexponential decay that persisted after NMDAR block (Fig.…”
Section: Pharmacological Composition Of Glutamatergic Endbulb Currentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Subsequently, STDP requires postactivation, which occurs through the generation of a somatic sodium (Na + ) spike that propagates back into the dendrites (Winters and Golding, 2018 ). The briefly previously presensitized synapse is potentiated by the passing backpropagating spike, as these concurrent pre/post stimuli trigger the influx of calcium into the spike head of the synapse (Franzen et al, 2020 ; Kladisios et al, 2020 ). If it is an inhibitory synapse, it will be suppressed.…”
Section: Biologically Motivated Backgroundmentioning
confidence: 99%
“…In the simplest case, a single distant synaptic input is attenuated and low-pass filtered before it reaches the soma. A single EPSP remains below threshold, and most of the collective synaptic potentials are too weak on their own to trigger a somatic action potential, but some constellations have converging EPSPs that sum at the soma and trigger an AP (Kladisios et al, 2020 ). The dendritic calculation evaluates the threshold crossing condition as a function of the actual sum of EPSPs arriving simultaneously at the soma.…”
Section: Biologically Motivated Backgroundmentioning
confidence: 99%